Anxiety, Self-Esteem, Bullying, and Peer Problems as Correlates of Self-Harm Behavior Among Adolescents in Kampar Regency, Riau Province, Indonesia - Alini, Alini; Said, Faridah Mohd; Aprilla, Nia; Nofrika, Bri (Media Publikasi Cendekia Indonesia, 2025)
Adolescents are a vulnerable population experiencing significant psychological and social changes, often leading to emotional difficulties and maladaptive behaviors such as self-harm. This study aims to analyze the associations and predictive factors of bullying, self-esteem, anxiety, and peer relationship problems with self-harm behavior among high school students in Kampar Regency, Riau Province, Indonesia. A cross-sectional study was conducted, involving 678 adolescents aged 15–18 years who met the inclusion criteria. Data were collected using validated structured questionnaires, including the Olweus Bullying Scale, Rosenberg Self-Esteem Scale, Hamilton Anxiety Rating Scale, and Peer Relationship Scale. Univariate analysis showed that 40% of respondents had experienced bullying, 30% had low self-esteem, 25% reported moderate to severe anxiety, and 35% had peer relationship problems. The prevalence of self-harm behavior was 18%. Bivariate analysis using the chi-square test revealed significant associations between all independent variables and self-harm behavior (p < 0.05). Multivariate logistic regression identified moderate to severe anxiety as the strongest predictor of self-harm (OR 3.7; 95% CI: 2.3–5.8), followed by low self-esteem (OR 3.1; 95% CI: 2.0–4.9), bullying experience (OR 2.8; 95% CI: 1.9–4.2), and peer relationship problems (OR 1.8; 95% CI: 1.2–2.9). These findings establish a clear evidence base for developing comprehensive, school-based psychosocial interventions aimed at mitigating these specific risk factors to reduce the prevalence of self-harm among adolescents in Kampar Regency, Riau Province, Indonesia.